4-H Afterschool Resource Guide: Developing and Managing a 4-H Afterschool Program - Sharon Junge; Vanessa Spero; Laura Valencia; Niki Crawson; J. R. Davis; Tara Dorn; Stacy Hall; Karen Henry; Heather Janney; Beth Kerr; Andrea Lazzari; Abby Morgan; et al. (EDIS)
This guide will assist Extension professionals in establishing new after-school programs in communities with insufficient programs available for school-age youth. The chapters cover a range of steps and considerations, including conducting needs assessments, hiring and training staff, and program sustainability. However, this guide cannot cover everything required. Additional resources that provide more in-depth information and tools are listed in this publication. The original educational material was edited and revised for this edition by the National Association of 4-H Youth Development Professionals Afterschool Working Group, led by Vanessa Spero.